AUTOMATIC DRIP IRRIGATION CONTROL SYSTEM USING PRIESTLEY-TAYLOR REAL-TIME APPROACH FOR INDOOR AND SCREEN HOUSE CULTIVATION OF CAISIM (BRASSICA RAPA SUBSP. CHINENSIS) - Prasasya, Radyani
One of the most common mistakes in irrigating vegetable crops is the provision of water that is not suitable for soil and environmental conditions. This study aims to design an automatic drip irrigation control system and logic for vegetable crops based on ESP32 in real-time and can be monitored remotely with the Google Firebase device. The model plant used was Caisim or choy sum (Brassica rapa subsp. Chinensis). In this study, an evaluation of water management in the control logic of the system was also carried out, namely the use of Priestley-Taylor (PT) reference evapotranspiration (ETr) bases with modified crop coefficient (Kc) values, dual crop coefficient, and the use of soil moisture sensors for single cultivation bases middle phase caisim (15-40 HSS). Modeling of Kc values is carried out for natural lighting conditions in the screen house and artificial lighting in the room. Empirical data collection was carried out by comparing the PT evapotranspiration basis treatment with Kc regression (T1), PT evapotranspiration basis with Kc dual coefficient (T2), the use of soil moisture sensors with a threshold of 37.96% (T3), and a fixed daily water volume of 828 ml ( T4). The best treatment combination is shown by caisim plants planted at screen house locations with water treatment based on Priestley-Taylor evapotranspiration with a single Kc regression modification, namely with an average net weight of 252 grams and water use efficiency of 305%. Further data analysis resulted in a mathematical model for the value of water demand with Kc regression for indoor locations, namely Irrigation = 0.2114 + 0.000235 ETr PT and at screenhouse locations, namely Irrigation = 0.7494 + 0.14274 ETr PT. On the other hand, the water demand value model with Kc dual coefficient for indoor locations is Irrigation = ETr PT (0.118HST + 0.2364), and at the screen house location, namely Irrigation = ETr PT (0.1086HST + 0.0606).